2020
DOI: 10.7226/jtfm.26.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Forest Utilization for Sustainable Livelihood through Community-Based Ecotourism in Kao Village of North Halmahera District

Abstract: This article aims to describe the mangrove forest utilization for sustainable livelihood through a community-based ecotourism approach. This research conduct in Kao Village, North Halmahera District of Indonesia. This study was done in a qualitative method using a life-history approach. The data was collected through in-depth interviews, observation, and document study. The data were analyzed using a triangulation method to obtain credible information. These research findings show that cultural value, known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(47 reference statements)
0
17
0
3
Order By: Relevance
“…Mangrove ecosystems provide ecosystem goods such as wood, food and medicinal compounds (Walters et al 2008;Mojiol et al 2016). On the other hand, the aesthetic value of mangrove forests has potential for ecotourism purposes which support community livelihood (Friess 2017;Singgalen 2020). In terms of climate change, mangrove has been considered one of the most effective carbon sequestration areas for reducing greenhouse gasses in the atmosphere and mitigating global warming (Heriyanto and Subiandono 2016;Maher et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove ecosystems provide ecosystem goods such as wood, food and medicinal compounds (Walters et al 2008;Mojiol et al 2016). On the other hand, the aesthetic value of mangrove forests has potential for ecotourism purposes which support community livelihood (Friess 2017;Singgalen 2020). In terms of climate change, mangrove has been considered one of the most effective carbon sequestration areas for reducing greenhouse gasses in the atmosphere and mitigating global warming (Heriyanto and Subiandono 2016;Maher et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ecotourism model emphasizes collaboration between stakeholders. It indicates that a participatory approach is an essential part of realizing the goals of destination development [12], [26], [27]. Furthermore, [28] showed that the development of mangrove ecotourism areas would be effective if carried out with a participatory approach to reduce the possibility of damage to mangrove forests due to human negligence.…”
Section: Mangrove Ecotourism In Dodola Island: Tourism Stakeholders A...mentioning
confidence: 98%
“…Tourists who visit mangrove tourism destinations generally have a goal of recreation or relaxation, considering the ecological conditions of the mangroves that produce fresh air, making it suitable for tourists who want to meditate or rest from busy work. According to an ecotourism approach, Indonesia is an archipelagic country with potential mangrove areas to be developed into tourist destinations [12]. Therefore, information systems management is needed to optimize the organizational goals that control the ecological, economic, and local socio-cultural balance.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, a collaborative approach can optimize the socio-economic and socio-ecological dimensions. Singgalen (2020) shows that in the context of North Maluku Province, especially the people in Kao Village-North Halmahera Regency, local norms and traditions can control collective behavior in utilizing mangrove forest resources. It is manifested in community support to rehabilitate mangroves and support the essential ecosystem zone or kawasan ekosistem esensial (KEE) program.…”
Section: Index Vegetation Of Guraping Mangrove Area 2013-2021mentioning
confidence: 99%